2015
DOI: 10.1002/anie.201508678
|View full text |Cite
|
Sign up to set email alerts
|

Enzymatic Synthesis of Nucleic Acids with Defined Regioisomeric 2′‐5′ Linkages

Abstract: Information‐bearing nucleic acids display universal 3′‐5′ linkages, but regioisomeric 2′‐5′ linkages occur sporadically in non‐enzymatic RNA synthesis and may have aided prebiotic RNA replication. Herein we report on the enzymatic synthesis of both DNA and RNA with site‐specific 2′‐5′ linkages by an engineered polymerase using 3′‐deoxy‐ or 3′‐O‐methyl‐NTPs as substrates. We also report the reverse transcription of the resulting modified nucleic acids back to 3′‐5′ linked DNA with good fidelity. This enables a … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
16
0

Year Published

2016
2016
2019
2019

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 24 publications
(18 citation statements)
references
References 38 publications
0
16
0
Order By: Relevance
“…Recently, Holliger and co-workers (Cozens et al, 2015 ) engineered the polymerase TGLLK (TgoT: Y409G, I521L, F545L, E664K), which proved to be effective at fully replacing purine dNTPs and NTPs with their respective 3′-deoxy or 3′- O -methyl analogs with defined 2′-5′ linkages allowing template-directed synthesis and reverse transcription of oligonucleotides with mixed 2′-5′/3′-5′ backbone linkages, expanding the repertoire for future in vitro evolution experiments.…”
Section: Polymerases For Nucleotides Bearing Sugar Modificationsmentioning
confidence: 99%
“…Recently, Holliger and co-workers (Cozens et al, 2015 ) engineered the polymerase TGLLK (TgoT: Y409G, I521L, F545L, E664K), which proved to be effective at fully replacing purine dNTPs and NTPs with their respective 3′-deoxy or 3′- O -methyl analogs with defined 2′-5′ linkages allowing template-directed synthesis and reverse transcription of oligonucleotides with mixed 2′-5′/3′-5′ backbone linkages, expanding the repertoire for future in vitro evolution experiments.…”
Section: Polymerases For Nucleotides Bearing Sugar Modificationsmentioning
confidence: 99%
“…Although there were slight differences in efficiency, generally SFM4‐3, SFM4‐6, and SFM4‐9 were more active (Figure S4). This is the first study to evaluate Taq mutants for this activity, and it showed that they can synthesize a 2′ linkage; previously only one Tgo mutant had been shown to synthesize 2′ linkages . These experiments open the door to future engineering of Taq mutants for the synthesis of M‐DNA with 2′ linkages.…”
Section: Resultsmentioning
confidence: 79%
“…Interestingly, one of the modified nucleotides that was recognized with higher efficiency had a 3′ modification (3′=OMe); 3′‐modified nucleotides with reversible protecting groups have applications in high‐throughput sequencing and in synthesizing RNA with 2′ linkage . There is only one report of a Taq mutant that recognizes a 3′‐protected nucleotide; no Taq mutant recognizes 3′‐modified nucleotides with 2′OH modifications.…”
Section: Resultsmentioning
confidence: 99%
“…Primer-dependent RNA synthesis has a number of applications, as it obviates the need to initiate transcription with a 5 ′ -pppG and allows a wide range of chemical groups to be added during solid-phase synthesis of primers (e.g., divergent 5 ′ -cap chemistries and cap-proximal epigenetic modification such as N 6 ,2 ′ -O-dimethyladenosine [m 6 A m ] and 7-methylguanosine [m 7 G] [reviewed in Meyer and Jaffrey 2017]). Further engineering enabled incorporation of regioisomeric 2 ′ -5 ′ linkages into both DNA and RNA by replacement of purine dNTPs with 3 ′ -deoxy or 3 ′ -O-methyl (3 ′ OMe) analogs (Cozens et al 2015).…”
Section: Engineering Primer-dependent Rna Polymerasesmentioning
confidence: 99%